Has a warm North Atlantic contributed to recent European cold winters? - Keenlyside, Noel; Omrani, Nour-Eddine (Environmental Research Letters, 2015)
The rise of global surface temperature waned during the last decade, despite increasing greenhouse gas concentrations. The temperature changes were most pronounced over northern hemisphere land masses during winter (Cohen et al 2012). They were largely associated with weakening of the mid-latitude westerly flow. To some, these temperature changes may seem paradoxical in the light of anthropogenic global warming, and thus there is much interest in explaining them. Peings and Magnusdottir (2014 Environ. Res. Lett. 9 034018) provide evidence that recent warming of the North Atlantic sea surface temperature (SST) may be part of the explanation. publishedVersion